2017
DOI: 10.1002/mnfr.201700297
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Potential Risks of Food Allergy and Toxicity of Soy Leghemoglobin Expressed in Pichia pastoris

Abstract: ScopeThe Soybean (Glycine max) leghemoglobin c2 (LegHb) gene was introduced into Pichia pastoris yeast for sustainable production of a heme‐carrying protein, for organoleptic use in plant‐based meat. The potential allergenicity and toxicity of LegHb and 17 Pichia host‐proteins each representing ≥1% of total protein in production batches are evaluated by literature review, bioinformatics sequence comparisons to known allergens or toxins, and in vitro pepsin digestion.Methods and resultsLiterature searches found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…28 , 29 Previously, the LegH and Pichia proteins within LegH Prep were evaluated for potential risk of allergenicity and toxicity in accordance with the CODEX Alimenterius Commission 2003/2009 guidelines for genetically modified foods and for novel food ingredients. 30 The analysis included literature search, sequence homology comparison to known allergens and toxins, and sensitivity to pepsin digestion in a simulated gastric fluid. There was no evidence in the scientific literature to suggest allergenicity or toxicity for these proteins, and the LegH protein sequence did not contain significant homology to any known allergens or toxins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 , 29 Previously, the LegH and Pichia proteins within LegH Prep were evaluated for potential risk of allergenicity and toxicity in accordance with the CODEX Alimenterius Commission 2003/2009 guidelines for genetically modified foods and for novel food ingredients. 30 The analysis included literature search, sequence homology comparison to known allergens and toxins, and sensitivity to pepsin digestion in a simulated gastric fluid. There was no evidence in the scientific literature to suggest allergenicity or toxicity for these proteins, and the LegH protein sequence did not contain significant homology to any known allergens or toxins.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, the authors of this study concluded that there was no evidence to suggest that food products containing LegH Prep posed any significant risk of dietary allergy or toxicity to consumers. 30 …”
Section: Introductionmentioning
confidence: 99%
“…The company Perfect Day Inc. (San Francisco, CA, USA) is developing animal-free dairy products through the production of animal milk proteins in yeast cultivated on a sugar feedstock (Pandya et al 2016), although this process could also employ CO 2 -derived feedstocks such as methanol or acetic acid. Impossible Foods Inc. (Redwood City, CA) has developed a strain of transgenic yeast containing a gene from soy for production of the protein leghemoglobin (Fraser et al 2018;Jin et al 2018), which is used as an ingredient in plant protein-based meat substitutes in order to mimic the flavors, aroma and cooking properties of real meat. The recombinant leghemoglobin produced by Impossible Foods Inc. has been designated Bgenerally recognized as safe( GRAS) by the US Food and Drug Administration (FDA 2018) and plant-based meat-imitation products containing recombinant leghemoglobin are already commercially available for human consumption under the Impossible™ brand.…”
Section: Possible Routes Towards Producing Edible Microbial Biomass Fmentioning
confidence: 99%
“…The full activity of this CGTase can be preserved for months with optimized chemical mixture (25% glycerol, 10% polyethylene glycol 400, and 0.5 mmol/L CaCl 2 ) as stabilizer . K. phaffii is a famous heterologous protein production host because its strong and strict expression mechanism of alcohol oxidase 1 promoter, high yield of heterologous protein (22 g/L intracellular production and 15 g/L secretory production), high cell density fermentation to 130 g/L, and general regard as safe status . Currently, there are roughly 1,000 heterologous protein successful expressed from K. phaffii with 70 of them are approved by U.S. FDA …”
Section: Introductionmentioning
confidence: 99%
“…10 K. phaffii is a famous heterologous protein production host because its strong and strict expression mechanism of alcohol oxidase 1 promoter, 11,12 high yield of heterologous protein (22 g/L intracellular production 13 and 15 g/L secretory production 14 ), high cell density fermentation to 130 g/L, 15 and general regard as safe status. 16,17 Currently, there are roughly 1,000 heterologous protein successful expressed from K. phaffii with 70 of them are approved by U.S. FDA. 18 To obtain recombinant K. phaffii strains, it is recommended to use a complex medium name buffered glycerol complex medium (BMGY) to cultivate recombinant K. phaffii because of fast growth of K. phaffii in BMGY medium.…”
mentioning
confidence: 99%